If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(x + 4) + 13 = -2x + -11 Reorder the terms: -3(4 + x) + 13 = -2x + -11 (4 * -3 + x * -3) + 13 = -2x + -11 (-12 + -3x) + 13 = -2x + -11 Reorder the terms: -12 + 13 + -3x = -2x + -11 Combine like terms: -12 + 13 = 1 1 + -3x = -2x + -11 Reorder the terms: 1 + -3x = -11 + -2x Solving 1 + -3x = -11 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 1 + -3x + 2x = -11 + -2x + 2x Combine like terms: -3x + 2x = -1x 1 + -1x = -11 + -2x + 2x Combine like terms: -2x + 2x = 0 1 + -1x = -11 + 0 1 + -1x = -11 Add '-1' to each side of the equation. 1 + -1 + -1x = -11 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = -11 + -1 -1x = -11 + -1 Combine like terms: -11 + -1 = -12 -1x = -12 Divide each side by '-1'. x = 12 Simplifying x = 12
| (y-z-b)-(b+y+z)= | | (7262x)+(1.26a)-(2844x-8.23a)= | | 2x^5+7x^4-10x^3-53x^2-28x+28= | | (72.62x)+(1.26a)-(2844x-8.23a)= | | 8(2x-9)=2(8x+6) | | 3x^3=32 | | 9+11z-3=5z+69-3z | | -3(x-1)-7=4x-11 | | 18+3y=9y | | (24.2x)+(8.25)+(83.6x-2.92)= | | 4x=28-0.25(4-16x) | | 5n-6(n+2)=14 | | -8(3x-4)+1=15 | | 5s+3s=56 | | (2x+6a)-(4x-a)= | | 8x=14-0.5(10x+2) | | 2z=-10 | | 61=16+5(x-3) | | 4.2q-5.9-5.5q=-2.3q-3.6 | | 8p=2(p+9) | | 8(w-2)= | | 100.39=28.90+49.99+2x | | (2x+5)+(x-2)= | | a+(a+450000)=625000000 | | 38.5=2x-1.5+2x-1.5+x+x+x+7.2 | | 33.9ab-82.4ac+29.3ad-84.8ac+73.2ab= | | y-17=-33 | | 2x-20=36.37 | | 9.9x+38.57=-10.1+38.41b | | 108=x+x+3.5x+3.5x | | Y^2+2y-24=0 | | 66.8=2x+4.7+2x+4.7+2x+4.7+2x+4.7 |